Attention-Deficit Hyperactivity and Obsessive-Compulsive Symptoms in Adult Patients With Primary Restless Legs Syndrome: Different Phenotypes of the Same Disease?. Issue 3 (4th May 2019) - Ghorayeb, Imad; Gamas, Ashley; Mazurie, Zoé; Mayo, Willy
ABSTRACT: Objectives : To investigate the prevalence of attention deficit hyperactivity disorder (ADHD) and obsessive-compulsive disorder (OCD) symptoms in adult patients with primary restless legs syndrome (RLS) and to determine the iron biological correlates of these comorbidities. Participants and Methods : We obtained demographic and clinical data from consecutive 105 outpatients with idiopathic RLS who answered validated questionnaires designed to assess the presence of ADHD and OCD symptoms. In these patients, iron blood parameters were routinely checked. Results : Of the total sample, 42.86% of the patients with RLS showed symptoms reminiscent either of ADHD or OCD. Prevalence of ADHD and OCD symptoms was 27.62% and 7.62%, respectively. Compared to other groups, a significantly higher percentage of RLS patients with ADHD symptoms was on antidepressant ( p = 0.012); and women with ADHD symptoms, either alone or combined with OCD symptoms, showed significant reduced ferritin concentrations compared to men with either isolated ADHD symptoms or with combined ADHD and OCD symptoms ( p = 0.028 and p = 0.025, respectively). Conclusions : Our findings highlight the high prevalence of ADHD and OCD symptoms in adult patients with primary RLS and independently of serum iron stores decrease, except for women with ADHD symptoms either alone or in combination with OCD symptoms. This may suggest an overlapping neurobiological dopaminergic and serotoninergic dysfunction in ADHD, OCD, and RLS, and question the expression of different RLS phenotypes. The efficacy of dopamine agonists in these groups of patients should be questioned in future studies.